2020
DOI: 10.1111/dth.13363
|View full text |Cite
|
Sign up to set email alerts
|

Severe de‐novo palmoplantar and nail psoriasis complicating Nivolumab treatment for metastatic melanoma

Abstract: Nivolumab, a fully human IgG4 immune checkpoint modulator, binds to the programmed cell death 1 (PD‐1) receptor on T cells and blocks their inhibition. Thus, it increases the anticancer host immune response by allowing T cells to attack tumor cells. Although anti‐PD‐1 immunotherapy is typically well accepted, deregulation of immune tolerance caused by nivolumab may determine immune‐related adverse events, among which skin toxicities represent the most common. We report a case of severe new‐onset palmoplantar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Although not systemically investigated, they are characterised by a late time of onset, extended up to several months. In some cases, lesions may persist after drug ICI discontinuation 84 . A wide range of nail changes (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not systemically investigated, they are characterised by a late time of onset, extended up to several months. In some cases, lesions may persist after drug ICI discontinuation 84 . A wide range of nail changes (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, lesions may persist after drug ICI discontinuation. 84 A wide range of nail changes (Fig. 7a-c) has been reported in association to ICI treatment: lunular erythema, onychorrhexis, thinning of the nail plate, fragility, longitudinal fissures, splitting in layers, onycholysis and onychomadesis.…”
Section: Nail Diraesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Yano et al reported that HLA-DR15, which is reported to correlate with autoimmune disease via IL-17 regulation, could be a predictive marker for ICI-induced secondary adrenal insufficiency [ 78 ]. Since both IL-17 and sCD163 reportedly correlate with autoimmune skin diseases such as bullous pemphigoid [ 79 ], psoriasis [ 80 ] and alopecia areata [ 81 ], and these autoimmune skin diseases were occasionally induced by ICIs in melanoma patients [ 82 , 83 , 84 ], HLA genotyping before treatment may help to avoid the incidence of irAEs by ICIs.…”
Section: Clinical Use Of Icis In the Treatment Of Advanced Melanommentioning
confidence: 99%
“…We read with interest the case report in Dermatologic Therapy by Altobrando et al entitled severe de-novo palmoplantar and nail psoriasis complicating nivolumab treatment for metastatic melanoma. 2 We report a case illustrating how PD-1 inhibitors can complicate the clinical picture in the setting of malignancy. Histopathology can be helpful in distinguishing between these two diagnoses.…”
Section: A Challenging Acral Psorasiform Eruption In the Setting Of Pmentioning
confidence: 99%